Imunomodulação por Actigen® em tilápia-do-nilo (Oreochromis niloticus): Respostas fisiológicas e desempenho produtivo após desafio com LPS - Ha, Natalia [UNESP] (2015)
Actigen® is a prebiotic containing active fractions of mannan rich proteins and due to its role in immunomodulation improves growth performance and intestinal health. The active fractions of mannan rich proteins are derived from the cell wall of yeast Saccharomyces cerevisiae, easily added to the diet of fish, and their use in fish production systems has promoted better performance indices beyong compensating the common undesirable effects of stress in fish farming. Studies of the effects of active fractions of mannan rich proteins in diets for fish are still recent especially regard the standardization of administration route, dosage and diet for each species. The aim of this study was to evaluate the effects of different concentrations of ACT on the immune responses of livestock, physiological and performance of Nile tilapia after challenge with lipopolysaccharide (LPS). The experiment was carried out in the Aquaculture Laboratory of UNESP, Dracena, where 288 juvenile tilapia (12 animals/box) were used in a completely randomized design with 4 treatments (0%, 0.04%, 0.06% and 0.08% ACT) and 6 replications. Two experiments were conducted, in the first were two biometrics at 30 and 60 days of experiment, with collections of two fish blood samples per box in each period. The second experiment was carried out after 60 days, in which the fish were challenged by intraperitoneal injection with LPS and after 5 and 12 days after inoculation, blood samples were collected from two fish per box. The growth performance, immunological, hematological and biochemical parameters were measured. The results obtained were subjected to analysis of variance (ANOVA) and means compared by Tukey test (5%), using the statistical program SAS, version 9.0. The active fractions of mannan rich proteins administration showed some positive effects on the immune parameters, indicating a possible beneficial action in order to ...